Sedentary Behavior Reduction: A Stepwise Approach to Increasing Physical Activity and Reducing Cardiovascular Disease Risk in Endometrial Cancer Survivors - Lauren C. Bates; Margaret I. Damare; Erik D. Hanson; Justin B. Moore; Victoria Bae-Jump; Michelle L. Meyer; Lee Stoner (Reviews in Cardiovascular Medicine, 2022)
Endometrial cancer survivors experience high rates of cardiovascular disease (e.g., heart disease, obesity, diabetes). The heightened cardiovascular disease risk may be attributed to cancer treatment coupled with sub-optimal lifestyle behaviors following treatment, including high amounts of sedentary behavior (SB). Public health agencies have graded the association of evidence between SB and cardiovascular disease as strong. However, while clinicians may wish to prescribe SB substitution strategies to reduce SB, guidelines do not currently exist. An additional challenge to behavior change pertains to the unique barriers that endometrial cancer survivors face, including treatment-associated fatigue and limited self-efficacy. Engaging in healthy movement behaviors, including minimizing SB and achieving recommended amounts of physical activity, are critical for health and well-being as well as cardiometabolic disease prevention. The purpose of this perspective paper is to propose an informed approach to physical activity promotion aimed to initiate movement and promote long-term behavior change by starting with an emphasis on reducing SB in endometrial cancer survivors. First, we address why endometrial cancer survivors should be targeted with SB reduction. Then, we suggest a stepwise approach to increasing physical activity by starting with SB reduction, including consideration to behavioral theories. Finally, we provide suggestions for future directions.